Mudik Dalam Perspektif Budaya Dan Agama (Kajian Realistis Perilaku Sumber Daya Manusia) - Abdul Hamid Arribathi; Qurotul Aini (UNIVERSITAS RAHARJA, 2018)
Idul Fitri is synonymous with homecoming, becomes a necessity and as if obligations which if left will be sinful and there is something missing. Yet mudik not known in Islamic teachings. In other words mudik original traditions and culture of Indonesia. The problem: is the culture of going home in accordance with the teachings of Islam and is it true Islam came to destroy the local culture ?. This paper aims to explain and convince the reader that the homecoming is original Indonesian culture, but still in accordance with the teachings of Islam and Islam came not to erode and destroy the local culture, but to straighten. This study is a normative legal research that is descriptive. The method used by the normative juridical method. Secondary data sources used include primary legal materials, secondary law materials and tertiary legal materials. The data obtained are then sorted to obtain data, verses and hadiths related to the rule of law which are then connected with problems encountered and systematized so as to produce a classification in harmony with the problems in this study. Furthermore, the legal material obtained is processed by deductive qualitative to arrive at the conclusion, so that the subject matter studied in this research will be able to be answered.